(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The research aimed to identify the effect of the difference between two blended learning strategies in developing the skills of designing websites among third-year secondary school students. The researcher used the quasi-experimental approach to answer the research questions. The research sample consisted of (60) third-year secondary school students at Imam Al-Tirmidhi High School in Al-Qunfudhah Governorate. The sample was divided into two experimental groups according to the experimental design of the research. They learned with two different blended learning strategies: - The first experimental group: explanation in the classroom followed by training on the Internet. - The second experimental group: explanation on the Internet followed by training in the classroom. The research tools were represented by an achievement test related to the cognitive aspect of the skill and a skill performance observation card. The research reached the following results: - There is no statistically significant difference at the level (0.05) between the average scores of students of the two experimental groups in the achievement test related to the cognitive aspect of the skill. - There is a statistically significant difference at the level (0.05) between the average scores of students of the two experimental groups in the skill performance observation card in favor of the first experimental group. Based on the results of the research, it can be recommended to start with the traditional method in blended learning strategies when teaching skills in order to prepare students to deal with electronic content. The researcher also concluded that making educational material available online on an ongoing basis helps in mastering the skill. He also suggested a number of topics to be included in the study in the future.